En indkapslet menneskehed: Autisme som en neuropolitisk metafor - Carlsen, Linus Nicolaj (K&K - Kultur og Klasse, 2025)
This paper studies the figural operationalization of autism as a specific configuration of elements in the early era of its clinical and cultural consolidation. The paper argues that the figuralization of autism is centered around the notion of mechanicity, a trope that was in general circulation in psychiatric, philosophical, sociological, and historical texts in the post-WWII US. By raising the question of figuralization, the paper also seeks to understand how metaphors taken from pathology can migrate from one discursive formation to another: how and why does a psychiatric diagnosis become a metaphor for modern life? Analyzing an excerpt from an exemplary text – American historian Lewis Mumford’s The Pentagon of Power (1970) – the paper aims to demonstrate how current metaphoric co-optations of autism are reliant upon a historically entrenched configuration that casts autistic individuals as affectless robots withdrawn from a shared emotional space. As such, autism as a ‘sticky’ metaphor is involved in, and owes its longevity to, a metaphoric network that came into being in a specific cultural and geographical situation. I argue that the importance of such historical figuralizations lie in the ways in which they help to police the boundaries of normative behavior and of the human as such.